Bulb Quality and Storability of Onion (Allium cepa L.) as Affected by Varieties and Intra-Row Spacing in Antsokia Gemza, Ethiopia - Asmirew, Birtukan; Gedamu, Yohannes; Ayalew, Asrat (Turkish Journal of Agriculture - Food Science and Technology, 2020)
This experiment was conducted in Antsokia Gemza district, Ethiopia in 2017/18 to evaluate the effect of intra-row spacing on bulb quality and storability of onion varieties. A 4×4 factorial experiment with four different varieties (Adama Red, Bombay Red, Melkam and Shendi) and four levels of intra-row spacing (5.00, 7.50, 10.00 and 12.50 cm) was laid on randomized complete block design with three replications. Data were collected on bulb quality attributes and storability and subjected to Analysis of Variance (ANOVA) using statistical analysis system (SAS) computer software 9.1. The mean separation test was done by list significant difference (LSD) test at 5% probability level. Simple linear correlation analyses between and among the different parameters were made using Pearson Correlation Coefficient. Accordingly, most of the parameters were significantly affected by intra-row spacing and variety. Variety Melkam exhibited the highest bulb diameter, bulb length, bulb dry matter content and bulb fresh weight. Melkam and Adama Red were with the lowest weight loss in storage while Bombay Red and Shendi scored the highest weight loss in storage. Most of the bulb quality parameters were significantly highest at the widest intra-row spacing of 10.00 and 12.50 cm. However, there was no significant variation between 7.50 and 10.00 cm intra-row spacing on average bulb weight which is considered as the most important bulb quality parameter for the producers from the market point of view. Weight loss was higher at the widest intra-row spacing for all varieties. Based on the findings of this study, it can be concluded that the bulb quality and storability of onion in Antsokia Gemza district can be optimized through cultivating variety Melkam at intra-row spacing of 7.5 cm.